Pengaruh Likuiditas Dan Profitabilitas Terhadap Return Saham Pada Perusahaan Subsektor Migas - Uci Oktavia; Dewi Sutjahyani (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
This study aims to examine the effect of liquidity and profitability on stock returns of oil and gas subsector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Stock return is a crucial indicator for investors in evaluating investment performance, particularly in the oil and gas subsector, which is characterized by high volatility due to fluctuations in global energy prices, macroeconomic conditions, and geopolitical dynamics. Liquidity in this study is proxied by the Current Ratio (CR) and Quick Ratio (QR), while profitability is measured using Return on Assets (ROA) and Return on Equity (ROE). This research adopts a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method and is analyzed with SmartPLS software. The research sample consists of 10 oil and gas subsector companies selected through purposive sampling based on consistent listing status and the availability of complete financial reports throughout the observation period. The analysis results indicate that liquidity has a negative and significant effect on stock returns, suggesting that excessively high liquidity may reflect inefficient utilization of current assets in generating shareholder value. Meanwhile, profitability shows a positive but insignificant effect on stock returns, indicating that higher profitability does not necessarily lead to higher stock returns. Simultaneously, liquidity and profitability explain 45.1% of the variation in stock returns, while the remaining proportion is influenced by other factors outside the research model. These findings imply that stock returns in the oil and gas subsector are not solely determined by internal financial performance but are also strongly affected by external factors such as global oil price movements, macroeconomic conditions, and market sentiment. This study is expected to contribute empirical evidence to financial literature and provide practical insights for investors in making informed investment decisions.